The economical rumours: origin and social functions - Pruskus, Valdas (Business: Theory and Practice, 2006)
In every presentation of information about economical phenomena there are always things which are understated differently by different people. This is determined by two factors: firstly, different intelligence, cultural experience, age, profession etc. of the people, secondly, different understanding of vocabulary (meaning of concepts). Thus, there is a difference between “knowing what it is” and “knowing about what it is”. A rumour is a means of not official communication and is concerned with not knowing what it is but with trying to explain “knowing about what it is”, on the grounds of not so much verified facts but rather on the feelings and speculations, put into a daily garment of understanding of concepts and information, adding, giving more or less meaning to one or another detail of the news by an individual himself. Thus, not official (non – verified) information can become (and becomes) more important than the official one. Being spontaneous, actually not controlled, it influences directly the general process of public communication, in its own way, giving it emotionality and making propagators of official information look for ways to convey their information in a much more precise, exhaustive, thorough way, not needing additional explanations, though (in the form of rumours) it is not easy to avoid them completely. There also exist objective reasons of origin and spreading of economical rumours in the society. First, shortage of information on a specific subject which is of interest and importance to the society. That is not announcing the events by the mass media; intentional mispresentation of the information being given by journalists due to various reasons and interests; public distrust of mass media, journalists, politicians, government authorities and official information conveyed by them; trying to achieve their goals by interested groups and individuals in spreading malicious information. Second, lack of information concerning specific issue for that individual. Third, fast spreading of scientific and technological inventions over different spheres of life, the understanding of which requires corresponding official presentation not in the form partly given by rumours. Spreading of economical rumors in wide sections of the population and social groups show that they also perform very important social functions. First, they help the group and an individual form and save social (including national) identity. Second, they strengthen integrity of the social group. Third, they influence decision making in case of different types of conflicts between business organizations. Fourth, they help the individual and the group achieve their goals. Fifth, they help the parties provoke actions which would be useful to one of them. Sixth, they help someone mislead the opponent. Seventh, they give the individual additional information in unclear and dangerous situations, thereby increasing one’s possibilities to better react to a new situation. Eighth, they decrease social alienation, encourage informal mutual personal contacts and cooperation. Existence of an economical rumour together with official verified information, exerting stronger or weaker influence upon all strata of social groups shows, on the one hand, its discrepant power, but on the other hand, its amazing viability, conditioned by its dual nature. Article in Lithuanian. Ekonominiai gandai: kilimo priežastys ir socialinės funkcijos Santrauka. Didėjant visuomenės kritiškumui įvairių ekonominių institucijų ir verslo organizacijų teikiamos informacijos atžvilgiu ir siekiant gauti vis daugiau ir „tikresnių” žinių, auga neformalios informacijos poreikis ir žinių galia. Tarpasmeninio bendravimo metu perteikta informacija sudaro palankią terpę gandams tarpti įvairiose žmogaus veiklos ir gyvenimo srityse. Gandai tampa svarbia priemone ir konkurencinėje kovoje, kuria naudojasi ir verslo organizacijos, jų grupės, ir pavieniai asmenys, siekdami įgyvendinti savus tikslus. Kartu vis labiau aiškėja, kad ir sėkmė versle priklauso ne tik nuo gero verslo plano ir tinkamai parinktos darbuotojų komandos, bet ir gebėjimo atpažinti, įvertinti ir dorotis su skleidžiamais ekonominiais gandais. Straipsnyje analizuojamos ekonominių gandų atsiradimo ir plitimo priežastys. Parodoma, kad ekonominiai gandai atlieka ir svarbias socialines funkcijas. Tai iš dalies ir lemia jų gajumą. Kartu parodoma, kad ekonominių gandų plitimo (ir platinimo) „laisvė” nepastebimai gali virsti (ir virsta) paveikia „nelaisvės“ forma verslui, individui ir visuomenei. Veiksmingiausios priemonės, mažinant ekonominių gandų jų plitimą ir jų paveikumą, – valdžios ir verslo struktūrų skelbiamos ekonominės informacijos išsamumas, įvairovė ir jos pateikimo formos suprantamumas bei prieinamumas visuomenei. Reikšminiai žodžiai: verslas, ekonominiai gandai, informacija, komunikacija, verslo organizacija, socialinė grupė, interesų grupės, bendradarbiavimas, žiniasklaida.